2011
DOI: 10.1002/ajim.21033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal disorders among farmers: A systematic review

Abstract: Objective To determine the prevalence of musculoskeletal disorders (MSDs) among farmers and to establish the most common regional MSDs reported. Methods Comprehensive electronic searches of Pubmed, Web of Science, CINAHL, SCOPUS, EMBASE, Agris Database, and Cochrane Library were carried out using keywords for MSDs and farmers. Pooled estimates of prevalence with 95% confidence intervals were calculated for overall MSD prevalence and the most common regional MSDs reported. Results Twenty-four studies fulfilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
2
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 35 publications
(125 reference statements)
2
110
2
7
Order By: Relevance
“…Kothiyal and Yuen, [24]; Olendorf and Drury, [28] and Reneman et al [29] strongly pointed that forward bending and twisting posture imposes higher postural strain among the workers which might be the cause of discomfort in different body parts [23,30]. Osborne et al [31] studied on farmers and reported that lower back pain was the most common MSD among the farmers, followed by upper and then lower extremity MSDs. They also suggested that the prevalence of MSDs in farmers was greater than in non-farmer populations.…”
Section: Resultsmentioning
confidence: 99%
“…Kothiyal and Yuen, [24]; Olendorf and Drury, [28] and Reneman et al [29] strongly pointed that forward bending and twisting posture imposes higher postural strain among the workers which might be the cause of discomfort in different body parts [23,30]. Osborne et al [31] studied on farmers and reported that lower back pain was the most common MSD among the farmers, followed by upper and then lower extremity MSDs. They also suggested that the prevalence of MSDs in farmers was greater than in non-farmer populations.…”
Section: Resultsmentioning
confidence: 99%
“…There is consequently excess load on the musculoskeletal system of farmers, particularly in the lumbar region. One review paper focusing on farmers with musculoskeletal symptoms reported that the prevalence of low back pain is higher in these subjects than in nonagricultural workers 7) . The European Directive on Mechanical Vibration set down requirements for WBV in the form of a daily exposure action value 8) (EUEAV) in 2006.…”
mentioning
confidence: 99%
“…Because clinical approaches exist for blocking IL-6 [45,46], future studies could investigate the role of IL-6 in modulating bone deterioration induced by chronic airway inflammatory agents. Our studies are focused on the lungbone axis because of the high prevalence of bone and airway disease in agricultural workers [9][10][11]. However, these data might have broader implications for understanding adverse systemic manifestations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-thirds of agriculture workers develop respiratory diseases (e.g. rhinosinusitis, asthma, chronic bronchitis, COPD) [6][7][8][9], and nearly 90% suffer from musculoskeletal disease, including high fracture rates [10][11][12]. Recently, we established an animal model demonstrating that intranasal inhalation of organic dust extract (ODE) collected from large animal (swine) confinement facilities and its microbial components induce systemic bone loss [13].…”
Section: Introductionmentioning
confidence: 99%